Four Different Methods as Applied to 5x5 Order in AXYZ Type Molecules - SAMPATH KRISHNAN, S.; N. SANKAR, B.; D. RAJAN, R.; GNANASEKARAN, S. (Asian Journal of Chemistry, 2010)
The potential energy constants of hydrogen isocyanate (HNCO) and its isotopically substituted molecule (DNCO) are calculated on the basis of General Valence Force Field. The interaction coordinates, coriolis coupling constants and rotational distortion constants of the molecules are also computed by four different methods and presented in this paper.